(untitled) (Progressive Agriculture, 2013)
The fresh mushroom and mushroom powder were analysed for their composition. Mushroom powder was incorporated in the formulations of cake at 0, 5, 10, 15 and 20% by weight. The effect of various levels of mushroom powder on the physico-chemical properties and nutritional quality of cakes had been observed. Mushroom powder at 15% addition level significantly improved colour, flavour and texture of cake. Cakes were also prepared by incorporating various levels (0-20%) of mushroom powder in plane cake formulations to evaluate optimum level of powder addition. It was observed that in achieving acceptable cake quality, in terms of volume significantly higher amount (10-15%) of mushroom powder could be incorporated in cake formulations. Compositional analysis of cake showed that cake containing mushroom powder had higher protein and fat content and lower carbohydrate content than the control cake. The cakes containing various levels of mushroom powder were evaluated for their sensory attributes by a panel of 10 tasters. The results revealed that the colour and flavour of cake containing mushroom powder was significantly different from the control cake. The texture of the cakes with mushroom powder was equally acceptable to the control cake. The overall acceptability of the cakes with mushroom powder was equally acceptable to the control cake. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16769 Progress. Agric. 21(1 & 2): 205 - 214, 2010